Liver transcriptome and physiological analyses preliminarily revealed the adaptation mechanisms of Amur grayling (Thymallus arcticus grubei, Dybowski, 1869) fry for dietary lipid nutrition - Fan, Ze; Ma, Kai; Wang, Yan; Wang, Liansheng; Zhang, Yongquan; Li, Chenhui; Li, Jiaxin; Wu, Di; Li, Jinnan; Li, Zhengwei (Frontiers in Veterinary Science, 2024)
The Amur grayling (Thymallus arcticus grubei Dybowski, 1869), a species of potentially economic and research value, is renowned for its tender meat, exquisite flavor, and high nutritional contents. This study involved a 56-day feeding trial with diets containing varying lipid levels (9.07%, 12.17%, 15.26%, 18.09%, 21.16%, and 24.07%, designated as GL1 through GL6, respectively) to explore the impact of dietary lipids on growth performance, intestinal digestion, liver antioxidative function, and transcriptomic profiles in Amur grayling fry (with average initial weight 4.64±0.03 g). The group receiving 18% dietary lipid exhibited a markedly higher weight gain rate (WGR) and specific growth rate compared to other groups, alongside a reduced feed conversion ratio (FCR), except in comparison to the 15% lipid group. Activities of lipase in pancreatic secretion and amylase in stomach mucosa peaked in the 18% lipid treatment group, indicating enhanced digestive efficiency. The liver of fish in this group also showed increased activities of antioxidative enzymes and higher levels of glutathione and total antioxidative capacity, along with reduced malondialdehyde content compared to the 9% and 24% lipid treatments. Additionally, serum high-density lipoprotein cholesterol levels were highest in the 18% group. Transcriptomic analysis revealed four significant metabolic pathways affected: Cholesterol metabolism, Fat digestion and absorption, PPAR signaling, and Fatty acid degradation, involving key genes such as Lipase, Lipoprotein lipase, Fatty acid-binding protein, and Carnitine palmitoyltransferase I. These findings suggest that the liver of Amur grayling employs adaptive mechanisms to manage excessive dietary lipids. Quadratic regression analysis determined the optimal dietary lipid levels to be 16.62% and 16.52%, based on WGR and FCR, respectively. The optimal dietary lipid level for juvenile Amur grayling appears to be around 18%, as evidenced by improved growth performance, digestive function, balanced serum lipid profile, and enhanced liver antioxidative capacity. Exceeding this lipid threshold triggers both adaptive and potentially detrimental liver responses.